Taxation and Migration by the Super-Rich - Arun Advani; David Burgherr; Andy Summers (Institute of Labor Economics (IZA), 2023)
Using administrative data on the globally connected super-rich in the UK, we study the effect of a large tax reform on migration behaviour. Prior to 2017, offshore investment returns for 'non-doms' – individuals tax-resident in the UK but with connections to other countries – were untaxed. People making use of that tax status are strongly concentrated at the top of the income distribution: 86% are in the UK top 1% and 29% in the top 0.1% once overseas investment income is taken into account. A reform in 2017 brought long-stayers, who had been in the UK for at least 15 of the last 20 years, into the standard tax system, reducing their effective net-of-average-tax rate by 18%. We find that emigration responses were modest: our central estimate is that the emigration rate increases by 0.26 percentage points for a 1% decline in the net-of-tax rate, and we can rule out increases larger than 0.4 percentage points. Dispelling fears that the targeted taxpayers were able to circumvent the tax hike, we find large average increases in income reported and tax paid in the UK of more than 150%.
Keywords: F22; H31; J61; 330; taxation; migration; capital income; inequality; mobility